Pinkalicious : puptastic ! - Kann, Victoria (New York : Harper, 2013)
Pinkalicious finds that her family will be dog sitting a poodle named Pinky for a week, but when Pinky arrives, the little poodle heads for a safe spot under the sofa and won't come out.
Ages 4-8.
Keywords: Pink -- Juvenile fiction; Poodles -- Juvenile fiction